1997
DOI: 10.1111/j.1399-6576.1997.tb04669.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodilution significantly decreases tolerance to isoflurane‐induced cardiovascular depression

Abstract: isoflurane-induced cardiovascular depression had adverse effects on cardiac output and oxygen delivery during extreme hemodilution because: 1) The vasodilatory effect of isoflurane was insufficient to compensate for the myocardial depression, and also contributed to a critically low arterial blood pressure; 2) A decrease in cardiac output produced delivery-dependent oxygen consumption and hyperlactemia; and 3) A decrease in myocardial blood flow caused myocardial ischemia which may have exacerbated the myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…In contrast, another study by the same group in the identical porcine model demonstrated a progressive decrease in CO and SVR resistance with increasing isoflurane concentrations. 18 This decrease in CO and SVR was greater after hemodilution. At isoflurane concentrations greater than 1%, arterial lactate concentrations also increased.…”
Section: Original Contributionsmentioning
confidence: 96%
“…In contrast, another study by the same group in the identical porcine model demonstrated a progressive decrease in CO and SVR resistance with increasing isoflurane concentrations. 18 This decrease in CO and SVR was greater after hemodilution. At isoflurane concentrations greater than 1%, arterial lactate concentrations also increased.…”
Section: Original Contributionsmentioning
confidence: 96%
“…Isoflurane, an anesthetic agent known to promote vasodilatation, causes a depression of CO and Q O 2 and an earlier fall in MAP during extreme hemodilution (49). Increased depth of anesthesia, with halothane or ketamine, also reduces the tolerance for hemodilution in rats (62).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the CI and cardiac output were measured using the Swan-Ganz catheter. Anesthesia was maintained with balanced anesthesia using isoflurane at a low concentration and fentanyl to avoid cardiovascular depression, because with severe anemia tolerance to volatile anesthetic-induced cardiovascular depression might be limited [11][12][13]. In other words, balanced anesthesia with a volatile anesthetic at low concentrations and fentanyl, which is known to decrease the minimum alveolar concentration of volatile anesthetics [14], may help stabilize hemodynamic parameters by minimizing noxious sympathetic responses during surgery [15] and by avoiding a decrease in the cardiac output induced by a high concentration of volatile anesthetic.…”
Section: Discussionmentioning
confidence: 99%